Financial Statements’ Disclosure in the Electronic Federal Gazette And Proprietary Concerns: A Differential Disclosure Framework for Policy Makers and Exploratory Evidence on Effects Dependent on Size, Ownership and Diversification - Grottke, Markus; Löffelmann, Johann V.; Haendel, Felix; Späth, Thomas (Journal of Business and Legal Sciences / Revista de Ciências Empresariais e Jurídicas, 2016)
We develop a framework for discussing regulatory activity in the area of differential disclosure systems. In particular, we define differential disclosure systems as being composed of three elements. The first element consists of the pieces of information that are unregulated and, therefore, subject to a market solution. The second element is made up of those pieces of information that are regulated and, therefore, subject to a compulsory disclosure requirement. Finally, the third element is the criteria that determine which pieces are regulated and unregulated for which firms, respectively. To illustrate the usefulness of our framework we examine the repercussions of the Electronic Federal Gazette that was introduced in Germany in 2007. In particular, we present exploratory empirical findings from an online survey of 126 small and medium-sized entities in Bavaria, a federal state of Germany. The survey participants’ ultimate judgment of the Electronic Federal Gazette turns out to be negative. They perceive it to be affected by the chosen solution in their business environment in various dimensions such as, for example, competition or price negotiations. We demonstrate that it is not size that accounts for their negative evaluation but rather the lack of diversification among those small and family-owned firms. Informed by these results, we discuss what might follow for different regulatory alternatives to assist policy makers in future regulations.